Analisis Putusan Terhadap Pelaku Tindak Pidana Penadahan Minyak Kelapa Sawit (Studi Putusan No. 238/Pid.B/2022/PN Mdn dan Putusan No. 653/Pid.B/2021/PN Mdn) - Arischa, Andini; Hidayani, Sri; Lubis, Anggreni Atmei (JUNCTO: Jurnal Ilmiah Hukum, 2024)
This article aims to examine the process of sentencing for perpetrators of palm oil fencing and the considerations made by judges in deciding on cases related to palm oil fencing, based on rulings No. 238/Pid.B/2022/PN Mdn and No. 653/Pid.B/2021/PN Mdn. Therefore, the focus of this article is on the elements of the criminal act, fencing, and palm oil. The research method used in this study is normative research. Data were collected through a literature review approach and were subsequently analyzed qualitatively. This study concludes that there are factors that influence the severity of the punishment imposed on the perpetrators of palm oil fencing. The sentence given for No. 238/Pid.B/2022/PN Mdn is imprisonment for 6 months under Article 480 paragraph 2 of the Criminal Code, while the sentence for No. 653/Pid.B/2021/PN Mdn is imprisonment for 2 years under Article 480 paragraph 1 of the Criminal Code. This sentencing serves as a preventive measure against similar crimes.